Mermaid Syndrome: A Case Report of a Rare Congenital Anomaly in Full-Term Neonate with Thumb Deformity - Taee, Nadereh; Tarhani, Fariba; Goodarzi, Mojgan Faraji; Safdari, Mohammad; Bajelan, Amir (American Journal of Perinatology Reports, 2018)
The mermaid syndrome (sirenomelia) is an extremely rare anomaly, an incidence of 1 in 100,000 births, in which a newborn born with legs joined together featuring a mermaid-like appearance (head and trunk like humans and tail like fish), and in most cases die shortly after birth. Gastrointestinal and urogenital anomalies and single umbilical artery are clinical outcome of this syndrome. There are two important hypotheses for pathogenesis of mermaid syndrome: vitelline artery steal hypothesis and defective blastogenesis hypothesis. The cause of the mermaid syndrome is unknown, but there are some possible factors such as age younger than 20 years and older than 40 years in mother and exposure of fetus to teratogenics. Here, we introduced 19-year-old mother's first neonate with mermaid syndrome. The mother had gestational diabetes mellitus and neonate was born with single lower limb, ambiguous genitalia, and thumb anomalies, and 4 days after birth, the neonate died due to multiple anomalies and imperforated anus.
Keywords: mermaid syndrome; sirenomelia; single lower limb; single umbilical artery; thumb deformity